MARKETING STRATEGY AND FINANCIAL LITERACY IN CONTEMPORARY COFFEE BUSINESSES IN MEDAN CITY - Fadila Zikri; Rina Asnita Damanik; Rosmawati Br Sipayung; M Ramadhani Syah Chandra; Fauzan Ananda H; Rukmini (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
The contemporary coffee business in Medan City is experiencing significant growth in line with the increasing lifestyle of urban people who make coffee not only as a consumption need, but also as part of social and lifestyle trends. This study aims to examine in-depth the marketing strategies applied by contemporary coffee businesses and how the level of financial literacy affects the management and sustainability of their businesses. The research used a descriptive qualitative approach with data collection techniques in the form of in-depth interviews with several coffee business owners and managers in Medan City, direct observation in the field. The results showed that although most business owners have been able to effectively utilize modern marketing strategies to increase brand visibility and sales volume, there are significant weaknesses in terms of business financial management. The low level of financial literacy means that many businesses do not have systematic financial reports, have difficulty separating personal and business finances, and have difficulty planning for business expansion. Therefore, improvement efforts are needed through training, workshops, and mentoring from related institutions. The integration of innovative marketing strategies with good financial management is believed to optimize the competitiveness and sustainability of contemporary coffee businesses Medan City.